2010
DOI: 10.1111/j.1600-9657.2009.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on traumatic dental injuries in preschool children at Kyung Hee Dental Hospital, Seoul, South Korea

Abstract: The purpose of this study was to analyse the traumatic dental injuries (TDI) of Korean preschoolers by investigating the occurrence, type, area, cause, injured region, seasonal variation and the interval between injury and treatment. In this study, data from 1856 preschoolers aged 4 months to 6 years and 11 months (mean age : 3.6 +/- 1.6) were used, out of a total of 2761 patients who attended the Department of Pediatric Dentistry, Kyung Hee Dental Hospital for TDI between January 1998 and December 2007. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
66
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 22 publications
26
66
2
5
Order By: Relevance
“…Th is fi nding is in agreement with previous reports 16,18,29 . Th e more urgent dental treatment is the result of bleeding tendencies and edema caused by soft tissue damage.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Th is fi nding is in agreement with previous reports 16,18,29 . Th e more urgent dental treatment is the result of bleeding tendencies and edema caused by soft tissue damage.…”
Section: Discussionsupporting
confidence: 93%
“…A lack of motor coordination 25,26 on walking and running is the main reason for TDI in preschool children, whereas in early school-age children, TDIs are most likely due to increased independence at school, playgrounds and sports 4,27,28 . In agreement with previous studies [18][19][20]29,30 , this study showed that TDI commonly involved maxillary incisors. Th is fi nding may be explained by the fact that these teeth may have inadequate lip coverage and frequently protrude 30 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Em lesões muito extensas e profundas, pode haver uma grande deposição dessa dentina na cavidade pulpar, ou a lesão de cárie pode induzir as células da polpa a produzirem focos de dentina no interior do tecido, podendo acarretar no aparecimento de calcificações pulpares capazes até de causar a obliteração da câmara 11 . Uma possível ruptura, mesmo que parcial, do suprimento vascular apical da polpa, após traumatismos alvéolo-dentários, pode gerar uma isquemia transitória ou a formação de um coágulo no tecido pulpar, com consequente depósito de tecido calcificado em decorrência da estimulação dos odontoblastos [12][13][14] . Da mesma forma que os traumatismos, porém com menor frequência, o tratamento ortodôntico representa estresse adicional para o tecido pulpar, que, numa tentativa de defesa, induziria a formação de calcificações 2,8,[15][16][17] .…”
Section: Introductionunclassified